Retrieving Aerosol Characteristics From the PACE Mission, Part 2: Multi-Angle and Polarimetry - Remer, Lorraine A.; Knobelspiesse, Kirk; Zhai, Peng-Wang; Xu, Feng; Kalashnikova, Olga V.; Chowdhary, Jacek; Hasekamp, Otto; Dubovik, Oleg; Wu, Lianghai; Ahmad, Ziauddin; Boss, Emmanuel; Cairns, Brian; et al. (Frontiers in Environmental Science, 2019)
The Plankton, Aerosol, Clouds, ocean Ecosystem (PACE) mission presents new opportunities and new challenges in applying observations of two complementary multi-angle polarimeters for the space-based retrieval of global aerosol properties. Aerosol remote sensing from multi-angle radiometric-only observations enables aerosol characterization to a greater degree than single-view radiometers, as demonstrated by nearly two decades of heritage instruments. Adding polarimetry to the multi-angle observations allows for the retrieval of aerosol optical depth, Angstrom exponent, parameters of size distribution, measures of aerosol absorption, complex refractive index and degree of nonsphericity of the particles, as demonstrated by two independent retrieval algorithms applied to the heritage POLarization and Directionality of the Earth’s Reflectance (POLDER) instrument. The reason this detailed particle characterization is possible is because a multi-angle polarimeter measurement contains twice the number of Degrees of Freedom of Signal (DFS) than does an observation from a single-view radiometer. The challenges of making use of this information content involve separating surface signal from atmospheric signal, especially when the surface is optically complex and especially in the ultraviolet portion of the spectrum where we show the necessity of polarization in making that separation. The path forward is likely to involve joint retrievals that will simultaneously retrieve aerosol and surface properties, although advances will be required in radiative transfer modeling and in representing optically complex constituents in those models. Another challenge is in having the processing capability that can keep pace with the output of these instruments in an operational environment. Yet, preliminary algorithms applied to airborne multi-angle polarimeter observations offer encouraging results that demonstrate the advantages of these instruments to retrieve aerosol layer height, particle single scattering albedo, size distribution and spectral optical depth, and also show the necessity of polarization measurements, not just multi-angle radiometric measurements, to achieve these results.